2011
DOI: 10.1007/s00414-011-0608-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the force associated with the formation of lacerations and skull fractures

Abstract: Publication informationInternational Journal of Legal Medicine, 126 (6) ABSTRACTPost mortem examination is often relied upon in order to determine whether a suspicious death was natural, accidental, suicidal or homicidal. However, in many cases the mechanism by which a single injury has been inflicted cannot be determined with certainty based on pathological examination alone. Furthermore the current method of assessing applied force relating to injury is restricted to an arbitrary and subjective scale (mild,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Similarly, a study conducted in England demonstrated that 26% of non-firearm related homicides involved blunt force trauma, 88% of which involved multiple blows to the head [2]. Another review of blunt force trauma cases over a period of 10 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) in Ireland demonstrated that 70% of blows resulted in both fracture of the skull and laceration of the scalp [3]. In Cape Town, South Africa homicide/assault is the second leading cause of premature death [4,5] and blunt force trauma forms a portion of these deaths [6].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, a study conducted in England demonstrated that 26% of non-firearm related homicides involved blunt force trauma, 88% of which involved multiple blows to the head [2]. Another review of blunt force trauma cases over a period of 10 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) in Ireland demonstrated that 70% of blows resulted in both fracture of the skull and laceration of the scalp [3]. In Cape Town, South Africa homicide/assault is the second leading cause of premature death [4,5] and blunt force trauma forms a portion of these deaths [6].…”
Section: Introductionmentioning
confidence: 94%
“…Typically, these take the form of case studies which merely describe the wound morphology due to specific weapons [26][27][28][29][30][31]. Only a limited number of studies have attempted to analyse the associated force behind an impact due to a specific blunt instrument [3,23,32,33].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, applying alternative methods rather than using animals has provided, in the forensic field, important and reproducible results, as presented in Table 3 [74,[77][78][79][80][81][82][83][84][85][86][87][88]. And for many less elaborate projects, animals who have died from other causes can be used.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, there was no finding indicating poor nutrition when the autopsy was performed. Thus, it is likely that the head injury was accidental rather than inflicted and that he had fallen down stairs, bruising the occipital area against the flat surface because there was some suture diastases without laceration [15].…”
Section: Discussionmentioning
confidence: 99%